2009
DOI: 10.1099/vir.0.008227-0
|View full text |Cite
|
Sign up to set email alerts
|

Profile of physical status and gene variation of human papillomavirus 58 genome in cervical cancer

Abstract: Epidemiological studies have shown that human papillomavirus 58 (HPV 58) is found at a relatively high frequency in east Asia and some regions of Central and South America. To investigate the physical status of HPV 58 and analyse sequence variations of HPV 58 in cervical cancer patients, the HPV 58 genome in 37 HPV 58-positive cervical cancer specimens collected from China were investigated by a mapping analysis based on nested PCR and nucleotide sequencing. A pure integrated genome was found in 78.4 % (29/37)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…8 The distribution of virus disruption sites in our study was consistent with that observation, with a range from nucleotide 1088 to 5057. Furthermore, considering the 2 main disrupted region discovered at E1 previously, the common disruption of the E1 gene in this study is no exception.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8 The distribution of virus disruption sites in our study was consistent with that observation, with a range from nucleotide 1088 to 5057. Furthermore, considering the 2 main disrupted region discovered at E1 previously, the common disruption of the E1 gene in this study is no exception.…”
Section: Discussionsupporting
confidence: 91%
“…5 Integration of HPV16 and 18 was widely studied, and their integrated sequences were determined in cell lines and clinical samples. 6 In addition, integration of HPV58 was identified in many infected patients with real-time polymerase chain reaction (PCR) by measuring the ratio of E2 to either E6 or E7 loads, 7,8 or with nested PCR with primer sets covering the whole HPV58 genome 9 ; however, owing to the limitations of those indirect methods, no viral-cellular junction could be identified. Likewise, there was no sequence information of viral disruption site and integration sites for HPV58.…”
mentioning
confidence: 99%
“…13 HPV 58 in our study showed variant lineages similar to those reported by previous studies. 19,20,22,23 HPV 58 C variant, a nonprototype variant in our study, could be found in eight (3.6%) of 220 HPV 58 samples in Hong Kong, 20 but not detected in 37 HPV 58 samples in Chengdu, China. 22 In Japan, the nonprototype of HPV 58 was observed in only one of 41 HPV 58 samples.…”
Section: Epidemiologymentioning
confidence: 90%
“…19,20,22,23 HPV 58 C variant, a nonprototype variant in our study, could be found in eight (3.6%) of 220 HPV 58 samples in Hong Kong, 20 but not detected in 37 HPV 58 samples in Chengdu, China. 22 In Japan, the nonprototype of HPV 58 was observed in only one of 41 HPV 58 samples. 23 In our study, nucleotide variations at positions 632 and 760 of HPV 58, resulting in amino acid change of T20I and G63S in E7, were linked in lineage A3.…”
Section: Epidemiologymentioning
confidence: 90%
See 1 more Smart Citation